KAJIAN ANTROPOMETRI PENGRAJIN TENUN IKAT KHAS MALUKU - Pattiasina, Nanse Henny; Markus, Pattiselanno; Pattiselanno, Steanly Reynold Romeo (JURNAL SIMETRIK, 2021)
Maluku Province is an Archipelago Province which consists of 1412 large and small islands. The availability of land resources in Maluku province is relatively limited. The total population in Maluku Province based on the Maluku Province BPS report until 2018, there were 1,773,776 people, of which Â± 25% were categorized as poor. This number occupies an area of 15,899.6 kmÂ² or only 7.6% of the total area of Maluku Province. Most of the population of Maluku inhabits the outermost islands in the districts of Southeast Maluku, West Southeast Maluku, and the Aru Islands or the outermost islands which are directly bordered by Timor Leste and Australia. Geographical conditions like this, affect the isolation due to limited transportation facilities and a dry climate, causing the income of the population here to be relatively low, although the potential for small industries and handicrafts has good prospects to be developed. One of the types of small industry that has the potential to be developed is the Maluku Ikat weaving industry, whose marketing has reached the export market. This product is in demand by foreign consumers because of its hand made characteristics, and is part of a creative industry that is very prospective in the future. The problem faced by this industry is its low productivity, on the other hand market demand continues to increase. This is because the work aids used are traditional tools that are not ergonomic according to the worker's body size, resulting in workers working in a sitting position on the work floor. For a work position like this will cause workers to feel tired quickly, and if done for a long time will cause health problems. The stages of the research include the survey process, the industrial selection stage, the measurement of worker anthropometric data and data analysis. The results showed that the anthropometry of workers based on leg height when sitting ranged from 38.15 to 48.99 cm, total height when standing ranged from 139.23 to 160.48 cm, body height when sitting ranged from 91.68 to 120.89 cm, arm length outstretched. (P26) ranged from 46.46 to 64.96 cm and flexed arm length (P16) ranged from 27.530 to 32.756 cm.